PENGARUH MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN TEMATIK DI KELAS IV SEKOLAH DASAR NEGERI 31 PONTIANAK BARAT - Maya, Rosami; Kartono, Kartono; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this study are: "Is there an effect of the discovery learning model on the learning outcomes of Social Sciences students in class IV State Elementary School 31 West Pontianak ?; How much influence does the discovery learning model have on the learning outcomes of Social Sciences students in class IV of State Elementary School 31 West Pontianak? The population in this study were students of class IVB 31 Elementary School in West Pontianak, totaling 35 people. Data collection uses measurement techniques in the form of multiple choice tests. The results obtained an average post-test 61.14 and 47.29 pretest. Based on the results of the t-test obtained tcount of 7.802 and 2.032 ttable. Because tcount> ttable, Ha is accepted, which means that there is an influence of the Scientific approach to the learning outcomes of Social Sciences in grade IV students of State Elementary School 31 West Pontianak. The results of the calculation of the effect size of 0.79 means that learning using discovery learning has a major effect on the learning outcomes of Social Sciences students in class IV State Elementary School 31 West Pontianak.Keywords: Discovery Learning Model, Learning Outcomes, Thematic